Pengaruh Kerja Sama Tim, Komunikasi dan Lingkungan Kerja Terhadap Kinerja Karyawan pada PT. Indo World Kabupaten Mojokerto - Rochman, Mochammad Saifur; Ubaidillah, Hasan; Andriani, Dewi; Rochmad, Mochmammad Saifur (Universitas Nusantara PGRI Kediri, 2024)
Human resources are one element in an organization, be it a private organization or a public organization. Human resources are the backbone of an organization. This research aims to determine the influence of teamwork, communication and work environment on the performance of employees located at PT. Indo World Mojokerto Regency. With a population of 932 employees, it is processed using the Slovin formula. And 100 employees were sampled. This research method uses quantitative. The data collection technique uses a Likert scale questionnaire. The sampling technique uses Simple Random Sampling Technique. Data analysis uses linear regression analysis. The data processing technique uses SPSS 26. Hypothesis testing uses the t test, f test. The results of this study show that the variables of teamwork, communication and work environment have partially positive and significant effects on employee performance at PT. Indo World. The variables of teamwork, communication and work environment also have a positive and significant effect on employee performance.